2021
DOI: 10.1111/ene.14915
|View full text |Cite
|
Sign up to set email alerts
|

Headache teleconsultation in the era of COVID‐19: Patients' evaluation and future directions

Abstract: Background and purpose Literature regarding headache teleconsultation and patient satisfaction is scarce. The SARS‐CoV‐2 pandemic led to the restructuring of traditional clinical activity by adopting telemedicine. Our objectives were to evaluate patients' satisfaction with headache teleconsultation by telephone during the SARS‐CoV‐2 pandemic and assess patients' preferred model of appointment (face‐to‐face, teleconsultation by telephone, or both). Methods Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
3
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
5
3
1
2
Order By: Relevance
“…Our results align with previous studies ( 28 , 30 , 33 ) with 67.3% of respondents expressing a preference for mixed-mode appointments in the future. Contrary to the United States, where only 7.1% of headache patients declined telemedicine ( 16 ), 29.0% of our respondents expressed a preference for exclusively in-person consultations in the future.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results align with previous studies ( 28 , 30 , 33 ) with 67.3% of respondents expressing a preference for mixed-mode appointments in the future. Contrary to the United States, where only 7.1% of headache patients declined telemedicine ( 16 ), 29.0% of our respondents expressed a preference for exclusively in-person consultations in the future.…”
Section: Discussionsupporting
confidence: 92%
“…An intriguing finding from our study emerged suggesting that respondents who had their primary neurology appointments remotely were less likely to choose teleconsultations in the future. A plausible explanation for this could be the absence of physical interactions, a component that patients often deem essential, underscoring the advantage of a hybrid approach that combines initial in-person consultations ( 13 , 29 , 30 , 33 ). Furthermore, our study revealed that patients who identified more disadvantages in telemedicine care and had lower evaluations of previous remote experiences with a general practitioner (GP) showed a greater preference for in-person visits.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this postvisit survey supports the claim of previous literature [1][2][3][4] that patients have a high level of satisfaction with telemedicine. Upon review of survey responses, especially free-text responses, patients appreciate the convenience of accessing the health care system virtually with EMCs.…”
Section: Comparison To the Current Literaturesupporting
confidence: 87%
“…The COVID-19 pandemic accelerated patient use and acceptance of telemedicine platforms. Multiple studies across different subspecialties have demonstrated patient acceptance of and satisfaction with telemedicine visits [1][2][3][4]. A survey of 7477 patients with type 1 diabetes in 89 countries found that 86% of respondents saw utility in virtual appointments and 75% planned to use telemedicine appointments again [5].…”
Section: Introductionmentioning
confidence: 99%
“…Lockdowns, remote work, and increased stress led to a surge in reported craniofacial pain cases [ 15 ]. Lately, virtual consultations, telemedicine, and tailored home-based exercises have become essential tools for managing pain while minimizing in-person interactions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%